Rand McNally new millennium world atlas deluxe [computer file]. ([Chicago] Rand McNally, 1998)
An interactive world atlas that offers a 3-D map base, as well as geographic, historic, and scientific content that can be explored with multiple navigation options, customizable maps, with styles for political, physical, and student maps that can be modified for relief and color, and 75 map features that can be turned on or off.
System requirements: Windows 95 or Windows NT 4.0, Pentium processor PC, 16MB of RAM, hard drive with 28MB of available space, 4X speed CD-ROM drive or faster, video adapter card and monitor that can display thousands of colours, internet features require a compatible browser and internet service provider.
Keywords: Atlases -- Interactive multimedia